Paediatric/adolescent stroke - Anuar, Muhamad Azamin (Springer, Singapore, 2024)
Childhood stroke is not uncommon. Data and research focussing on childhood stroke remains scarce and needs further study to improve access to health care and investigations including acute interventions and rehabilitation model. This chapter covers neonatal and paediatric strokes and outline aetiologies, investigations and interventions and rehabilitation management. Wide ranges of pathogenesis brought in this chapter to explain how stroke in neonates and pae diatric cohorts develop and pathways in managing them.